Geophysical investigation for 3D geological modelling and ore exploration in the Skellefte mining district - Tavakoli, Saman (Luleå tekniska universitet, Geovetenskap och miljöteknik, 2012)
The Skellefte mining district, northern Sweden, is regarded as one of the country’s richest mineral districts. Most of the outcropping deposits in this district or those deposits which are located at shallow depths (≤ 300 m) are likely to have already been discovered, which motivated the Swedish mining companies to expand their explorations at greater depths (e.g. ~5 km depth). Whereas previous explorations conducted in the central Skellefte district (CSD) contributed extensively to unveil VMS deposits, a comprehensive 3 and 4-dimensional geological model for ore exploration was lacking. The main aim of this study is thus to constrain and delineate geological structures at depth, using geophysical data for exploration of VMS deposits and create a well-constrained 3D geological model of the Skellefte district, northern Sweden. This is done in the framework of the project titled “4D-modeling of the mineral belts”. The deposits are volcanogenic massive sulphide (VMS) and the major deposits in the CSD contain commodities: Zn-Cu-Au-Ag and Pb. The deposits are generally characterized by higher magnetic susceptibility, density, chargeability and conductivity than many other rocks. This study thus includes magnetic, gravity and resistivity methods as main geophysical methods used. The results of seismic reflection data are integrated for joint geophysical interpretations and physical properties of the rocks, including density, magnetic susceptibility, resistivity and chargeability, have been measured.The thesis includes four studies: (i) local-scale study of the CSD using potential field, resistivity and induced polarization (IP) data, (ii) regional-scale potential field modeling to test seismic interpretations and improve the modeling of geological structures, (iii) understanding the geometry of the three early-orogenic intrusive bodies in the Holmträsk domain using potential field data, (iv) targeting VMS deposits using 2D and 3D resistivity/IP data in the CSD.Potential field modeling along three profiles where ...